Determination of the structure of a new potentially active pharmaceutical substance - T. V. Sotnikova; O. Yu. Strelova; E. P. Sanaeva; D. A. Kolesnik; I. P. Yakovlev (Разработка и регистрация лекарственных средств)
Introduction. The development of methods for analyzing new potentially active pharmaceutical substances is an important part of substance standardization. An integrated approach to confirming the structure of a substance is especially important when the substance may exist in different tautomeric forms, since the properties of the substance may change depending on tautomerism, affecting, among other things, the pharmacological activity.Aim. The aim of our study was to determine the tautomeric composition of the potential active pharmaceutical substance 5-butyl-6-hydroxy-2,3-diphenylpyrimidin-4(3H)-one in solid state and solution for the subsequent development of its dosage form and determination of bioavailability.Material and methods. The object of the study was the substance 5-butyl-6-hydroxy-2,3-diphenylpyrimidin-4(3H)-one. Spectra were taken to confirm the structure: infrared on a PerkinElmer Spectrum 3 device (PerkinElmer Inc., USA) in the frequency range from 4000 to 400 cm–1, nuclear magnetic resonance 1H and 13C on a pulsed broadband spectrometer Bruker AM-500 (400 and 100 MHz) (Bruker, Germany) in DMSO-d6 solvent, ultraviolet using SF-2000 (LLC "OKB Spektr", Russia) in the wavelength range of 250–400 nm, and high-performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS) was also carried out.Results and discussion. A feature of pyrimidine hydroxy derivatives is the presence of tautomeric forms, which can affect both the physicochemical properties of the substance and its pharmacological activity. The study found that in the solid state, 5-butyl-6-hydroxy-2,3-diphenylpyrimidin-4(3H)-one is in equilibrium between the diketo form and the enol form, and when the substance is dissolved in dimethyl sulfoxide (DMSO), the enol form is predominant. The purity was confirmed by HPLC-MS/MS.Conclusion. The structure of 5-butyl-6-hydroxy-2,3-diphenylpyrimidin-4(3H)-one was confirmed by IR and NMR spectroscopy. UV spectra were obtained, and HPLC-MS/MS was performed to exclude possible absorption of ultraviolet radiation by impurities.